Judicial enforcement of socio-economic rights under the 1996 constitution : realising the vision of social justice - Ngcukaitobi, T (Rhodes University, Faculty of Law, Law, 2003)
Few legal developments in South Africa and elsewhere in the world in recent times have excited such controversy as the legal recognition of social and economic rights. South Africa has created a special place for itself in world affairs for being one of the countries that recognise socio-economic rights in a justiciable Bill of Rights. Partly this is in response to the appalling levels of poverty prevalent in the country which could potentially destabilise the new democracy. Improvement of the quality of life of every citizen is a crucial step in consolidating the constitutional democracy. The question that will face any court in giving effect to socio-economic rights is: how are these rights to be judicially enforced in a given context? The crux of this thesis lies in the resolution of this question. Firstly this thesis traces the philosophical foundations to the legal recognition of socio-economic rights. It is stated that the recognition of these rights in a justiciable bill of rights requires a conceptually sound understanding of the nature of obligations that these rights place on the state. It is emphasised that it is imperative that access to justice be facilitated to poor and vulnerable members of society for the realisation of the constitutional goal of addressing inequality. Particular concern and priority should in this context be given to women, children and the disabled. The study explores various judicial remedies and makes suggestions on new and innovative constitutional mechanisms for judicial enforcement of these rights. It is concluded that there is an important role to be played by civil society in giving meaningful effect to socio-economic rights.
Keywords: South Africa. Constitution; South Africa. Bill of Rights; Civil rights -- South Africa; Human rights -- South Africa; South Africa -- Politics and government -- 1994-; South Africa -- Economic conditions -- 1991-; South Africa -- Social conditions -- 1994-